SISTEM INFORMASI PENANGANAN GANGGUAN VSAT PADA CUSTOMER BERBASIS JAVA DI PT SATKOMINDO MEDIYASA - Parulian, Dudi; Qadarsih, Nurmala Dewi; Putra, Willy Johan (Jurnal Sistem Informasi Kaputama (JSIK), 2020)
Technology and information are very fast making business activities increase, PT Satkomindo Mediyasa still has several systems that are still manual, it needs help sending technicians, so the level of problems in recording is very high. The purpose of this research is to support information systems that handle Java-based VSAT and design methods using Research and Development (R&D) methods. The results built on this information system collect the technician work report data so that it makes it easier for employees to manage technician work reports